Mitigating Strategies for Road Accidents in Nepal using IoT, AI and ML - Bhatt, Prakash Datt (Api Journal of Science, 2025)
Rapid deployment of Internet of Things (IoT) and increasing the number of active IoT devices connected in this network predicts 41billiondevices by 2030, double the number of devices connected now. This prominent technology is being used in every sort of applications, including transportation and traffic management systems. IoT has a significant impact on the safety road as well as accident detection and prevention systems. This paper explores the primary reasons of road accidents in Nepal, how the integration of IoT with AI solutions is embedded into vehicles to monitor and control road accidents, mitigate the number of accidents, and recommend the best IoT-enabled vehicle systems which are more compatible with the roads in mountain and hilly regions like Nepal. Mainly, sentimental analysis to observe the mind-state of the driver and alert the concerned bodies by using cloud-based services is the major concern. Later, using ultrasonic sensor and sensor boards in the sharp turn of the mountain detects another vehicle is arriving from the opposite side, or any obstacles is presented nearby and suggests controlling their speed to minimize the accident is another finding. Additionally, face detection and object counting cameras, alcohol detection sensor can also reduce the road accidents by reporting real-time mistakes due to human misbehavior. Finally, the integrated effect of deploying all aforementioned technologies has been computed which seems better than individual’s performance. This integrated solution can be proven milestone for reducing the number of accidents in the mountainous road system of Nepal.